Covid-19, chaos theory and “the drop of honey effect”. Viruses and human behavior - Filipe, J. (Estudios de Economía Aplicada, 2020)
The paper applies the “drop of honey effect” to the Covid-19 disease’s spread and to the timing for acting. The timing and level of the adopted measures are considered crucial in terms of the virus spread and of the health consequences for populations. The study allows to conclude that a small difference in the adoption of the most proper measures in the initial moment, as much as the measures’ level, may make all the difference in the consequences of the disease and in its pandemic effects, what is valid not only for the first moment after the disease appearance in China but also after its arrival to each country. The “drop of honey effect” is perfect to explain the way how this coronavirus spread all over the world after its detection in humans and to explain its effects. The consequences on the public health were devastating, with thousands of deaths. Also the social, economic and financial implications around the world were enormous, particularly with many stock exchanges declining severely as coronavirus spread.